Research and application of herbal medicine in the treatment of chronic kidney disease since the 21st century: A visualized bibliometric analysis - Xu, Yunling; Chen, Jia; Wang, He; Lu, Ying (Frontiers in Pharmacology, 2022)
Background: Here, a bibliometric and knowledge-map analysis was used to analyze the research status and application of herbal medicine for the treatment of chronic kidney disease (CKD). By looking for research hotspots and key topics, we provide new clues and research directions for future research. Methods: Articles and reviews regarding herbal medicine in the treatment of CKD were retrieved from the Web of Science Core Collection on 23 May 2022. The R-bibliometrix, VOSviewer, and CiteSpace software were used to conduct the bibliometric and knowledge-map analysis. Results: In total, 5,920 authors at 1,330 institutions from 68 countries published 1,602 papers in 355 academic journals. China is the leader and pioneer in the research and application of herbal medicine in the field of CKD treatment. Beijing University of Chinese Medicine contributed the most publications. Ping Li (China-Japan Friendship Hospital) published the most articles, while Yingyong Zhao (Northwest University) had the most cocitations. However, cooperation among countries and the research institutions is not sufficient. Journal of Ethnopharmacology published the most research and application of herbal medicine in the treatment of CKD and was the most commonly co-cited journal. The most influential research hotspots about herbal medicine in the treatment of CKD focused on diabetic nephropathy-related research, Balkan endemic nephropathy, and pharmacokinetic study. Conclusion: Herbal medicine has a wide range of pharmacological activities and therapeutic value. The research and application of herbal medicine for the treatment of CKD, especially diabetic nephropathy, will remain a hot topic in the future.